Modified Fractal-shaped Slotted Patch Antenna with Dipole-shaped Slotted Ground Plane with Enhanced Gain for X-band Applications - Samantaray D.; Bhattacharyya S.; Srinivas K.V. (My University, 2025)
This work concentrates on the design and working analysis of a modified fractal-shaped slotted patch antenna with defected ground plane designed for X-band applications. A shorting via at the centre of the slotted fractal patch and a dipole shaped slots at the ground plane have been used in the proposed design to enhance the gain of the antenna. The maximum return loss of 22 dB has been achieved at 11.25 GHz over the frequency range of 10.58-11.37 GHz while the maximum realized gain of 16.98 dB has been obtained at 10.78 GHz. The designed antenna offers broadside radiation characteristics. The proposed antenna can be utilized for X-band applications like defense applications, satellite communication and microimaging in medical analysis for determination of radio waves. © 2018 IEEE.